2021
DOI: 10.1016/j.esxm.2020.100317
|View full text |Cite
|
Sign up to set email alerts
|

Intracavernous Injection of Autologous Platelet-Rich Plasma Ameliorates Hyperlipidemia-Associated Erectile Dysfunction in a Rat Model

Abstract: Introduction Hyperlipidemia is associated with an increased risk of erectile dysfunction (ED) mediated by endothelial damage. Platelet-rich plasma (PRP) contains numerous angiogenic growth factors. Currently, evidence supporting the use of PRP for ED treatment is limited. Aim We investigated PRP in a rat model of hyperlipidemia-associated ED. Methods Thirty 2-month-old male Sprague–Dawley rats were randomly divided into 3 groups. 20 rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…These findings suggest that PRR can accelerate nerve regeneration and prevent corporal smooth muscle atrophy. Similar studies, with equivalent results have been conducted by Gur et al and Huang et al ( 32 , 33 ).…”
Section: Review Of the Current Evidencesupporting
confidence: 87%
“…These findings suggest that PRR can accelerate nerve regeneration and prevent corporal smooth muscle atrophy. Similar studies, with equivalent results have been conducted by Gur et al and Huang et al ( 32 , 33 ).…”
Section: Review Of the Current Evidencesupporting
confidence: 87%
“…PRP treatment for ED might be linked to cellular structural remodeling. Current research revealed that PRP is rich in growth factors such as fibroblast growth factor (FGF), PDGF, TGF-β, epidermal growth factor (EGF), VEGF, and insulin-like growth factor (IGF) ( 29 ). The plasma, abundant in nutrients, vitamins, hormones, electrolytes, and proteins, plays a pivotal role in cell survival, thereby being instrumental for cell differentiation and proliferation ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The plasma, abundant in nutrients, vitamins, hormones, electrolytes, and proteins, plays a pivotal role in cell survival, thereby being instrumental for cell differentiation and proliferation ( 30 ). Moreover, a couple of studies have reported that intracavernous injection of PRP in the corpus cavernosum post-cavernous nerve injury can alleviate ED by reducing markers of cell apoptosis and fibrosis ( 29 , 31 ). Hence, our study focused on examining the effectiveness and safety of PRP treatment for ED.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is a possibility that oxidative stress is connected to endothelial damage inside the cochlear microcirculation. 13 Tinnitus sufferers have higher plasma oxidative stress indicators and reduced antioxidant activity than healthy people. However, tinnitus research on antioxidant supplementation is scarce and inconsistent.…”
Section: Discussionmentioning
confidence: 99%